2016
DOI: 10.1007/s10661-016-5240-4
|View full text |Cite
|
Sign up to set email alerts
|

Landslides susceptibility change over time according to terrain conditions in a mountain area of the tropic region

Abstract: Susceptibility to landslides in mountain areas results from the interaction of various factors related to relief formation and soil development. The assessment of landslide susceptibility has generally taken into account individual events, or it has been aimed at establishing relationships between landslide-inventory maps and maps of environmental factors, without considering that such relationships can change in space and time. In this work, temporal and space changes in landslides were analysed in six differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…The implementation proposal of this methodology as a RILEWS would make it possible to forecast RIL occurrence zones, constraining how the precipitation thresholds under a RIL could take place. Our results could suit an operational RILEWS scale considering the geomorphological features and the distributed precipitation values above the place as a proxy [8,11,24,64].…”
Section: Modelingmentioning
confidence: 91%
“…The implementation proposal of this methodology as a RILEWS would make it possible to forecast RIL occurrence zones, constraining how the precipitation thresholds under a RIL could take place. Our results could suit an operational RILEWS scale considering the geomorphological features and the distributed precipitation values above the place as a proxy [8,11,24,64].…”
Section: Modelingmentioning
confidence: 91%
“…Vegetation plays a positive role in the stability of landslides and can improve the shear strength of the soil, while increasing the stability of the slope [ 58 ]. According to the observations of extensive field investigation, the more vegetation there is, the lower the number of landslides.…”
Section: Methodsmentioning
confidence: 99%
“…For the three LR models, by using new landslides as validation data, it is found that using updated predisposing factors (2020) significantly improves the model performance compared to using the predisposing factors from 2010. This is primarily due to the dramatic LUC and urbanization, which also impact the fundamental geological and environmental conditions, such as the NDVI, land use, and traffic conditions [30,76,77]. Meanwhile, the models exhibit their best performance when employing time-varying predisposing factors.…”
Section: Model Performance Comparsion and Future Prediction Of Lsa By...mentioning
confidence: 99%